2019
DOI: 10.3390/jcm8122025
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Eosinophil Cationic Protein Is a Diagnostic and Predictive Biomarker in Young Adults with Inflammatory Bowel Disease

Abstract: Background and Aims: Fecal biomarkers are important non-invasive markers monitoring disease activity in inflammatory bowel disease (IBD). We compared the significance of fecal eosinophil cationic protein (fECP) and fecal calprotectin (fCal). Methods: fECP and fCal were measured in patients with Crohn’s disease (CD, n = 97), ulcerative colitis (UC, n = 53), Clostridioides difficile infection (CDI, n = 9), primary food allergy (PFA, n = 11), pollen-associated food allergy (n = 25) and non-inflammatory controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Finally, ILDs 8 comprise a large group of diseases that generally affect the interstitium [31] and have been associated with increased levels of eosinophils in bronchoalveolar lavage fluid and serum [32,33], which work as cytokine mediators for acute and chronic inflammation, causing damage to lung tissues, myocardium, skin and gastrointestinal tract. [34][35][36][37] The positive association of EO% with the DRR in our cohort provides support for this mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, ILDs 8 comprise a large group of diseases that generally affect the interstitium [31] and have been associated with increased levels of eosinophils in bronchoalveolar lavage fluid and serum [32,33], which work as cytokine mediators for acute and chronic inflammation, causing damage to lung tissues, myocardium, skin and gastrointestinal tract. [34][35][36][37] The positive association of EO% with the DRR in our cohort provides support for this mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…Eosinophil PMD has been described in inflammatory conditions such as ulcerative colitis, allergic rhinitis and asthma patients 27 , by ultrastructural analysis as the loss of granular density without fusion of intergranular membranes and the increase in cytoplasmic secretory vesicles 41 . In those patients, the moderate to extensive degree of PMD 27 and the presence of extracellular and fecal eosinophil-derived cationic proteins suggest an inflammatory activation profile of eosinophils 5,[42][43][44] . In the present study, quantitative analysis demonstrated a low degree of PMD in jejunal eosinophils, being significantly higher in IBS-D respect to HC.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to basophils, IBD patients exhibit a pronounced infiltration of eosinophils in the mucosa, especially in UC patients, not only in active disease but also during remission. The presence of eosinophils has even led to suggest eosinophil-derived markers, such as eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) as fecal markers in IBD, complementary to calprotectin [ 84 , 85 ]. Mechanistically, it is considered that eosinophils are effector cells that contribute to barrier dysfunction through the release of pro-inflammatory cytokines and cytotoxic factors after degranulation.…”
Section: Type 2 Associated Immune Cells In Ibdmentioning
confidence: 99%